EFFICACY OF INSULIN, HEPARIN AND FENOFIBRATE COMBINATION TREATMENT IN SEVERE HYPERTRIGLYCERIDEMIA: DOUBLE CENTER EXPERIENCE - (:unkn) unknown (EDITURA ACAD ROMANE, 2019)
Context. Severe hypertriglyceridemia (SH), which calls for a triglyceride (TG) level above 1000 mg/dL, remains an important health issue. While some data exist to offer combination of heparin, insulin and fenofibrate as a reasonable treatment option, safety and benefits of this therapy have not been accurately weighted, largely due to the limited sample size of the relevant studies. Aim. Assess the efficacy and safety of the heparin, insulin and fenofibrate combination in the treatment of patients with SH. Patients - Methods. Patients aged >= 18 years with TG level above 1000 mg/dL and adequate organ function were included. Triglyceride levels were measured immediately before the treatment and on the 3rd and 6th days of the treatment. Treatment dosage, duration, response and side effects were assessed. Patients with hypertriglyceridemia presenting with acute pancreatitis were treated additionally with lipid apheresis. Results. A total of 42 patients were included. Of these, 85.8% came to medical attention with some kind of secondary hypertriglyceridemia causes. The baseline median TG value of the cases was 2141.0 mg/dL (1026-12250). There were 6 patients (14.3%) with acute pancreatitis at presentation. In patients without pancreatitis, with administration of insulin infusion, unfractionated heparin infusion and fenofibrate capsule, median TG values decreased to 921 mg/dL (190-6400) on the 3rd day and to 437 mg/dL (112-1950) on the 6th day of the treatment (p<0.0001, Friedman test). Potential toxicities related to insulin, heparin and fenofibrate combination treatment including hypoglycemia, hemorrhage, rise in creatine kinase levels, hepato - and nephrotoxicity were not observed. Conclusion. In this trial involving patients with SH, our data suggest that insulin, heparin and fenofibrate combination therapy was safe and effective.
Keywords: Hypertriglyceridemia; insulin; heparin; fenofibrate; PANCREATITIS CASE SERIES; AMERICAN SOCIETY; PLASMAPHERESIS; APHERESIS; GUIDELINES; MANAGEMENT